Inspiring a 'fourth revolution'? The modern revolutionary tradition and the problems surrounding the commemoration of 1917 in 2017 in Russia. Issue 247 (13th January 2017) - Rendle, Matthew; Lively, Anna
Abstract: There has been much written about the official commemorations of 1917 in Soviet Russia, but after 1991 the revolution became a contentious event and it is unclear how the state will commemorate the centenary. It is too big to ignore, but potentially dangerous politically. After the 'colour revolutions' and the Arab Spring, revolution has been associated with instability, violence and terror, and is used to justify increasingly authoritarian and interventionist domestic and foreign policies. This article examines Putin's speeches and the state's actions to suggest that the state may try to recast 1917 as a celebration of former imperial and Soviet power rather than as a short-lived democratic revolution.